Types of Readers and character at the Diario de lectura de los Escolios by Nicolás Gómez Dávila (2023)
In this text, I analyze the Diario de lectura de los Escolios de Nicolás Gómez Dávila, Cuadernos I y II, written by Ernesto Volkening. The main objective is to explore the essence of this text being labeled as a reading journal and the implications that arise from such categorization. Furthermore, I examine the various reader archetypes that emerge within this journal and delve into the portrayal of the narrative voice, which reflects Volkening’s perspective throughout the writing. This examination reveals Wolkening’s self-representation as a nostalgic and pessimistic individual who views philosophy as a means to safeguard the “spirit” from what he perceives as a tumultuous and estranging era. Finally, I raise queries concerning the absence of criticism toward the National Front, the period during which Volkening penned this diary.